TINGKAT PENERAPAN SAK EMKM PADA PELAKU UMKM DAN UPAYA PENINGKATAN PENERAPAN SAK EMKM DILIHAT DARI PERSEPSI UMKM DAN SOSIALISASI SAK EMKM - I Nyoman Sutapa (Faculty of Economics and Business, Universitas Warmadewa, 2020)
Micro, small and medium enterprises are still constrained by the collection of financial statements and if left unchecked it will have a negative impact on development, one of which is that development is low because it increases capital and will make it harder for banks to analyze the feasibility of credit assistance for users. The population in this study was 97.277 in Denpasar district by taking a sample of 100 companies randomly. Based on the results of the data analysis, it can be concluded that H1 was rejected because the Perception of SMEs did not oppose the adoption of SAK EMKM in the city of Denpasar and H2 was accepted because the SAK EMKM socialization was positively beneficial to the application of SAK EMKM in the city of Denpasar.